2019
DOI: 10.1177/0021909618820357
|View full text |Cite
|
Sign up to set email alerts
|

Constituting Agricultural and Food Security Policy in Malawi: Exploring the Factors that Have Driven Policy Processes in the Farm Inputs Subsidy Programme

Abstract: Political economy analyses of agricultural and food security policies in Malawi have emphasized the role played by domestic politics and, more specifically, the centralization of power in the executive. This paper builds on this perspective by exploring the view that such policies are in fact negotiated outcomes of interactions at the state–donor interface. Using interview data gathered from expert key informants and a review of publicly available data, the paper explores how certain policy drivers have intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Regarding the comments about government support for a universal programme as reported by Chinsinga (2012), we identified a tension amongst the views of government stakeholders. In keeping with prior literature documenting an interest among some stakeholders to target more ‘productive’ farmers [ 72 , 78 ], our government stakeholders frequently expressed a desire to target ‘productive’ farmers rather than something more universal. They suggested that issues of poverty and food insecurity could be addressed directly through other types of social support consistent with prior studies [ 72 , 94 – 98 ].…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…Regarding the comments about government support for a universal programme as reported by Chinsinga (2012), we identified a tension amongst the views of government stakeholders. In keeping with prior literature documenting an interest among some stakeholders to target more ‘productive’ farmers [ 72 , 78 ], our government stakeholders frequently expressed a desire to target ‘productive’ farmers rather than something more universal. They suggested that issues of poverty and food insecurity could be addressed directly through other types of social support consistent with prior studies [ 72 , 94 – 98 ].…”
Section: Resultsmentioning
confidence: 53%
“…This development may reinforce the dominant view that maize equals food security, but it could also maintain active stakeholder investments in maize seed as opposed to other cereals and legumes [ 77 ]. Whilst Nkhoma (2019) noted that the existing political environment may be the cause of policy oscillations [ 78 ], it could as well be the case that any nutritional impacts and improvements to dietary diversity were secondary to the economic and food-security objectives. There are three reasons for this.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high costs, obvious technical inefficiencies, and some evidence of politicization in the implementation of the FISP program have led to increased questioning of whether this is the best use of the significant public resources allocated to the program. Recognizing the potentially important opportunity costs for the overall development of Malawi associated with the inefficient implementation of FISP, coupled with a fiscal crisis for the government linked to withdrawal of donor financial support due to concerns about mismanagement, the government made reforms to the program starting in 2015/16 (Nkhoma, Bosman, and Eduful 2019). These included reducing the number of annual beneficiaries, from around 1.5 million farming households to 900,000, as well as the amount of subsidy farmers receive.…”
Section: Fertilizer Subsidiesmentioning
confidence: 99%